Risky Parental Practices and Their Implications in Adult Psychopathology (Studia Doctoralia Psychology and Educational Science, 2021)
There are many ways in which an individual may fail as a parent. Most parents have good intentions, but that’s the exact reason why there’s an urgent need to clarify good parenting practices. This paper will look at risky parenting practices (e.g., guilt-inducing criticism) and their relationship with psychopathology (depression and anxiety, in this case) using socially prescribed perfectionism as a mediator. All eight mediations turned out to be statistically significant with six out of eight analyses being full mediations. Also, the relationships between the facets of perfectionism, depression, and anxiety are consistent with the findings of other studies up until this point. Considering the relationship between socially prescribed perfectionism and psychopathology, practical implications are discussed.